PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS - Sherlyn, Sherlyn; Sudirgo, Tony (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze the effect of company size, profitability, and liquidity on firm value in sector manufacturing companies Consumer Non-Cyclicals listed on the Indonesia Stock Exchange during the 2019-2021. The sample selected in this study was a purposive sampling method with several selected criteria, so this study used data from 65 companies with a total of 195 samples. The data processing technique used is the IBM Statistical Product and Service Solution (SPSS) 29 and Microsoft Excel 2022 programs. The results of this study indicate that company size, profitability, and liquidity have a positive and significant effect on firm value. The implication of this research is the need to increase profits and the ability to pay obligations to increase the value of the company which will provide a good signal for investors.